The Approach of Islamic Da'wah in Global Education : A Thematic Analysis of Contemporary Challenges - Norddin, Muhammad Fikri; Wan Muda, Wan Hanim Nadrah; Halim, Fazlinda Ab; Saparuddin, Intan Farhana (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
The approach of Islamic Da'wah refers to the methods or techniques practiced by each individual who plays the role of a preacher in conveying Islamic teachings to others. However, any approach must inevitably have challenges that need to be overcome to ensure the successful implementation of the approach. Skills among preachers, especially educators using the Da'wah approach, are crucial to ensure that teaching and learning sessions can be conducted effectively in educational institutions in line with the current educational changes. Therefore, this article delves deeply into the Da'wah approach used in global education and the challenges in implementing the Da'wah approach in educational institutions. The results of the systematic analysis using the ENTREQ technique in the selection of 15 articles reveal the existence of 5 main themes covering the challenges of the Da'wah approach in education, namely the challenges of the Da'wah approach in technology, challenges in the implementation of the Da'wah approach, challenges in the content of the Da'wah approach, challenges of the Da'wah approach among the disabled and special needs individuals, as well as challenges in the acceptance of the Da'wah approach involving education. This article is also expected to serve as a guide for educators in conducting more effective teaching and learning activities based on the guidelines provided by the Ministry of Education (KPM) to ensure the country's education moves towards higher quality education in line with the Malaysian Ministry of Education Strategic Plan (PSKPM) 2024-2030, focusing on Core 1 in enhancing access and quality of education in Malaysia.